Maternal morbidity and mortality – Publications in The Peruvian Journal of Gynecology and Obstetrics during the 70 years of institutional life of the Peruvian Society of Obstetrics and Gynecology - Gutiérrez Ramos, Miguel (2017)
High maternal morbidity and mortality, which occur mainly in poor, developing countries, constitute a problem which is very representative of a country’s health system, and are therefore considered as leading health indicators. For this reason, although maternal mortality expressed in absolute values does not represent an exorbitant quantity for a country, every case represents a failure of the country’s health system. Cases of maternal morbidity are more numerous, which is why they could be more useful to enable the authorities to take more effective action to combat maternal death. This article analyzes the publications made in relation to investigations, reports and cases of maternal morbidity and mortality since 1950, that is, for the past 67 years.